Desperdício de alimentos em restaurantes: uma análise em uma instituição universitária - Deliberador, Lucas Rodrigues (2019)
About one-third of world food production is lost or wasted annually at different stages of agri-food production chains (APC). Food losses generally occur in the early stages of an APC, while waste is understood as the discarding of food that occurs in the final stages of APCs. Food losses and waste have important economic, environmental and social impacts worldwide. Thus, studying their causes, as well as strategies that minimize them, is among the central concerns of those who work with food at all levels and forms. Food in school settings, including restaurants in higher education institutions, is among the sectors that deserve special mention, as a result of generating significant quantities of food wasted by consumers. In this context, this research aimed to verify what causes that most influence the consumers of a university restaurant to waste food and what measures that could be taken to reduce this waste. The research used in its development a unique study realized in the university dining hall of a federal university. The aim was to analyze, through a structured questionnaire, the perceptions of consumers about different variables influencing food waste. The results were statistically correlated with the leftovers on the plates or trays of each consumer. An average waste of 68g/consumer was verified, which is considered high and superior to what is acceptable in the literature. This information was used to propose policies and actions that will seek to minimize the wastes found.